Geology, Petrology and Fracture Survey Of Granite In Lumut Area, Perak - Zulkifli, Muhammad Ridhwan (2016)
The final year project presents detailed geology, petrology and fracture survey of granite in Lumut outcrop which is named as the Dinding granite. The location of the project is situated around 25 km from the Ipoh-Lumut highway. The present work on the Lumut outcrop is generally to classify the various granite types as well as to validate the fractured system lead to stress identification. However, previous studies on the Dinding granite is used as reference and guidance. Field investigation and sample collection were carried out in the Lumut area. Preliminary study revealed that the granite can be classified into two main types, medium-grained porphyritic granite and fine-grained equigranular granite with substantial fractures. The samples collected will be analyzed. For fracture analysis, coarse-grain granite shows the dipping of fractures is in NE-SW direction, while it is in NW-SE direction for fine-grain granite. As for Uniaxial Compressive Strength, fine-grained granite has maximum stress of 21.56 MPa which is lower than coarse-grained granite, which is 66.91 MPa. Both type of granite achieve same result which is good rock for Rock Mass Rating result, and also show same mineralogical composition for both type of granites. For Magnetic susceptibility, fine-grained granite achieve higher value which is range from 123 – 160 x 10-6, while coarse-grained granite get lower value in between the range 46 – 105 x 10-6. From the testing of Schmidt Hammer, it is found that the average IRb or N reading is 37.94 for coarse-grained granite and 51.45 for fine-grained granite. In a nutshell, all this studies help to differentiate both type of granites in Lumut area, lastly help to achieve the objective of this study.